Courts and the environment - Voigt, Christina, 1971-; Makuch, Zen (IUCN Academy of Environmental Law, 2018)
This discerning book examines the challenges, opportunities and solutions for courts adjudicating on environmental cases. It offers a critical analysis of the practice and judgments of courts from various representative and influential jurisdictions. Through the analysis and comparison of court practices and case law across global domestic courts as varied as the National Green Tribunal in India, the Land and Environment Court in Australia, and the District Court of The Hague in the Netherlands, the expert contributors bring together a wealth of knowledge in order to enhance mutual learning and understanding towards an environmental rule of law. In doing so, they illustrate that courts play a vital role in the formation and crystallization of rulings and decisions to protect and conserve the environment. Ultimately, they prove that there are many lessons to be learnt from other legal systems in seeking to maintain and enhance the environmental rule of law. Contemporary and global in scope, Courts and the Environment is essential reading for scholars and students of environmental law, as well as judges, legal practitioners and policymakers interested in understanding the legal challenges to and the legal basis for protecting environmental values in courts.